Problemi dei contingenti all'importazione (The problem with import quotas) - V. BARATTIERI; A. DELLA GHERARDESCA; F. GALDI (Moneta e Credito, 2014)
Today trade policy and the politics of protectionism in Italy, for the most part carried out within the EEC, essentially rely on the Community system of customs duties on imported products and variable taxes on agricultural imports. However, there is also a set of domestic trade policy instruments, among which the system of quantitative import restrictions. The present article analyzes the economic, legal and practical aspects of the complex problem of the allocation of import licenses between national operators. In the first part the authors summarize the main differences between quotas and customs duties. The formulas adopted to date in Italy are then re-examined and the criteria used by the other CEE countries are referred to. Finally, the objectives identified as priorities in the field of Public Administration are specified, the main shortcomings of the current system highlighted and some changes proposed.